Factors That Influence The Utilization Of Community Health Center Services By National Health Insurance (JKN) Participants In The Muara Tembesi Community Health Center Working Area, Batang Hari Regency - Sundari, Sundari; Andy Amir; Dwi Noerjoedianto; Arnild Augina Mekarisce; Adila Solida (Sean Institute, 2024)
Backgroud: Equitable distribution of health services in Indonesia is still a big challenge, especially because of the country's geographical condition which consists of many islands. To overcome this, the Indonesian government has implemented various programs, including National Health Insurance (JKN) which is managed by BPJS Health. Puskesmas, as a first level health service, plays an important role in supporting the JKN program and improving the level of public health. Method: This research uses a quantitative approach with a cross-sectional design. The research was conducted in the working area of the Muara Tembesi Health Center, Batang Hari Regency, in September 2023 – November 2023. The research population was all people in the working area of the Muara Tembesi Health Center. The sampling technique used probability sampling with a total sample of 114 respondents. Data was collected through interviews and analyzed using the chi-square test. Result: The results showed a significant relationship between age (p-value=0.000, PR 95% CI: 2.204 (1.475-3.294)), occupation (p-value=0.022, PR 95% CI: 1.404 (0.979-2.013) ), education (p-value=0.005, PR 95% CI: 1.447 (1.071-1.954)), accessibility (p-value=0.000, PR 95% CI: 1.591 (1.262-2.005)), and perception of illness (p- value=0.008, PR 95% CI: 1.339 (1.086-1.651)) with utilization of community health center services. However, the availability of health workers did not show a significant relationship with the utilization of community health center services (p-value=0.524, PR 95% CI: 0.900 (0.735-1.103)). Conclusion: There is a relationship between the variables age, employment, education, accessibility, and perceptions of illness using Muara Tembesi health center services. Batang Hari Regency. Meanwhile, there is no relationship between the variable availability of health workers and the utilization of Muara Tembesi health center services. Batang Hari Regency